Root dynamics and interactions in a nutrient-poor and drying species-rich woodland - Teste, Francois Philippe (2016)
Climate change is decreasing the amount and delaying the start of winter rains in southern hemisphere Mediterranean ecosystems. Important components of western Australia’s Mediterranean biodiversity hotspot are the Proteaceae such as Banksia species. These plants rely on threshold-soil moisture levels to deploy their efficient nutrient-mobilising cluster roots to gather poorly-available nutrients from extremely phosphorus (P)-impoverished soils. The physiology of cluster-rooted plants has been well studied however their responses under climate change are largely unknown. We determined the root dynamics with minirhizotron measurements in a eucalypt-banksia woodland with or without irrigation to mimic the current reduced rainfall (based on long-term averages). Furthermore, we estimated the lifespan of the different root types, root intermingling, and cluster root P remobilisation. Irrigation produced a noticeable yet small increase in root production only in june. Standing crop was generally greater in non-irrigated plots and root mortality was independent of irrigation. Survival analyses of the different root types encountered with the cluster roots revealed considerable effects of soil depth on lifespan. Despite predictions from plant ecophysiological studies on the aboveground responses to a drying climate, we only found small transient effects on root production. However, there was a considerable effect of irrigation on the frequency of root intermingling and we suggest that root interactions may become less prominent under a drying climate. Root P remobilisation in cluster roots was efficient, only leaving ~10 354 % of P behind suggesting that if any form of nutrient-uptake facilitation takes place during root intermingling, it likely involves a form of kleptoparisitism. We propose that roots in this system and presumably other ecosystems show some resilience to a modified precipitation regime but this was not the case for interspecific root interactions. We suggest that if nutrient-uptake facilitative interactions decline under a drying climate so will root-driven mechanisms that promote plant species coexistence and the maintenance of diversity.